2018
DOI: 10.1038/s41433-017-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Slit lamps and lenses: a potential source of nosocomial infections?

Abstract: Bacterial species of the normal skin flora were isolated from the ophthalmological equipment. The bacterial contamination of the portable devices was significantly higher than that of slit lamps. Therefore, proper hygiene of the mobile instruments should be monitored in order to prevent transmission of bacteria in residents and consultants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This is in line with previous findings for spectacles and microscope oculars, where we found largely the same dominant taxa. We could also prove the presence of staphylococci, which matches the cultivation-based detection of coagulase-negative staphylococci by Sobolewska et al (Sobolewska et al, 2018). While they identified staphylococci as the most frequent bacteria on slit lamps, we found this genus in lower proportions, which may be due to the use of different methods.…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with previous findings for spectacles and microscope oculars, where we found largely the same dominant taxa. We could also prove the presence of staphylococci, which matches the cultivation-based detection of coagulase-negative staphylococci by Sobolewska et al (Sobolewska et al, 2018). While they identified staphylococci as the most frequent bacteria on slit lamps, we found this genus in lower proportions, which may be due to the use of different methods.…”
Section: Discussionsupporting
confidence: 88%
“…These may be due to production and material defects during manufacturing or may have occurred during packaging and shipping. Even if vigilance against volatile particles and aerosols is increased during these days of the COVID-19 pandemic [ 6 ], smooth surfaces or inorganic materials may contain bacterial deposits and contamination [ 7 , 8 ]. It was shown that by no means must the patients' own conjunctiva be regarded as the only source of potential contamination but also the material used [ 9 , 10 ] and the oral flora of the staff [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goldmann-type contact lenses, laser surgery lenses, gonioscopy lenses, and others] are vectors for nosocomial infection during an ophthalmologic examination. 40,41 In order to limit the number of patients coming into contact with a single lens, many ophthalmology departments, including our own, have suspended the use of trial lenses and trial framing, and are only performing refractions in rare situations. 28 Singleuse diagnostic or therapeutic lenses, such as those offered by some manufacturers (eg, Volk Optical and Katena), can reduce the potential for transmission of infection and eliminate the time required for disinfection without affecting image quality.…”
Section: Lensesmentioning
confidence: 99%